M5C-Related lncRNA Predicts Lung Adenocarcinoma and Tumor Microenvironment Remodeling: Computational Biology and Basic Science - Bai, Ming; Sun, Chen (Frontiers in Cell and Developmental Biology, 2022)
Abstract Purpose: RNA modification is a critical process in epigenetics that regulates post-transcriptional gene expression. There are several studies of m6A RNA methylation; however, many types of RNA modification regulate post-transcriptional gene expression, and reports on M5C RNA methylation are insufficient. Method: We considered m5C RNA transferase-related protein-coding genes. The long non-coding RNAs regulated by m5C RNA transferase were determined using Pearson correlation coefficients greater than 0.4. We divided TCGA-Lung adenocarcinoma (LUAD) into two lncRNA expression patterns regulated by m5C RNA transferase using non-negative matrix decomposition. Based on the WGCNA, we determined the biological process of both LncRNA expression patterns. LASSO regression was used to generate the m5C RNA transferase lncRNA prognostic model. Migration and proliferation assays were used to test the relationship between LINC00628 and tumor cell migration in NCI-H460 and NCI-H1299 cells. Results: 185 m5C RNA transferase-related lncRNAs were determined by pearson coefficient>0.4 . 16 prognostic-related lncRNAs were selected by univariate cox regression analysis. TCGA-LUAD were divided into two regulation modes of m5C RNA transferase using non-negative matrix factorization. The two regulation modes showed significant differences in overall and disease-free survival. GSVA revealed a close relationship among M5C score, ribosomes, endolysosomes, and lymphocyte migration. LASSO was applied to calculated an m5c-related lncRNA overall survival signature using LINC00628, LINC02147 and MIR34AHG. The m5C-lncRNA signature score closely related with overall survival in lung adenocarcinoma. Receiver operating characteristic curve and decision curve analysis verified the accuracy of the prognostic model. The cell migration and proliferation assay such as transwell experiments and wound healing assays suggested that the m5C RNA transferase-related lncRNA LINC00628 promotes the proliferation and migration of lung adenocarcinoma cell in NCI-H460 and NCI-H1299 cells. Conclusion: Three lncRNA expression patterns regulated by m5C RNA transferase were identified. A M5C related lncRNA overall survival signature was constructed. The prediction model of m5C transferase lncRNA provide some understanding of the influence of m5C transferase on lung adenocarcinoma. These results have potential clinical value in managing lung adenocarcinoma.